The Effectiveness of Using Playclock Media on Students' Critical Thinking Ability - Dian Novianti Sitompul; melyani sari sitepu; Arianto (Journal of Psychology and Instruction, 2024)
This research was motivated by teachers who were not used to using game-based learning media, which had an impact on students' low critical thinking abilities. The purpose of this research is to find out whether the use of clock media is effective on students' critical thinking abilities? This research is a quantitative research with a pretest-posttest one group design. Data collection techniques use tests. The research instrument uses a test sheet to see students' critical thinking abilities. Data were analyzed using Paired Sample T-Test. The results of the research show that the use of game-based rotating clock media is effective for students' critical thinking abilities. This can be seen from the paired t-test analysis data by comparing the sig<a (5%) values. The results of the analysis using SPSS show that the sig value is smaller than alpha (0.000<0.05). From the obtained sig values, it can be concluded that the use of rotating clock media is effective on students' critical thinking abilities